2021
DOI: 10.1155/2021/8034874
|View full text |Cite
|
Sign up to set email alerts
|

Brevibacterium Bacteremia in the Setting of Pyogenic Liver Abscess: A Case Report with Accompanying Literature Review

Abstract: A 71-year-old Pakistani man with poorly controlled type 2 diabetes mellitus presenting with worsening mental status, abdominal pain, and oral intake for the past seven days was found to have pyogenic hepatic abscess with unculturable bacteria and subsequently found to have rare Brevibacterium bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The Brevibacterium was found to be pyogenic as Kumar et al reported a patient who presented with neurological symptoms and was found to have a brain abscess [8] . Moreover, Hossain et al reported a case presented with bacteremia, and with further investigation, a liver abscess was discovered [15] . Furthermore, Eidensohn et al report a patient with osteomyelitis [3] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Brevibacterium was found to be pyogenic as Kumar et al reported a patient who presented with neurological symptoms and was found to have a brain abscess [8] . Moreover, Hossain et al reported a case presented with bacteremia, and with further investigation, a liver abscess was discovered [15] . Furthermore, Eidensohn et al report a patient with osteomyelitis [3] .…”
Section: Discussionmentioning
confidence: 98%
“…Most of the reported cases were treated with broad-spectrum antibiotics, such as vancomycin, teicoplanin, aminoglycosides, beta-lactamase, and fluoroquinolones [13] . However, despite the adequate treatment, 6 out of 20 cases report a recurrent infection of Brevibacterium [15] . Some reported patients had implanted catheters, where removing the implanted foreign body was impossible as it was critical to their underlying disease.…”
Section: Discussionmentioning
confidence: 99%